Development and Characterization of an Amorphous Solid Dispersion of Furosemide in the Form of a Sublingual Bioadhesive Film to Enhance Bioavailability - Viviana De Caro; Alessia Ajovalasit; Flavia Maria Sutera; Denise Murgia; Maria Antonietta Sabatino; Clelia Dispenza (MDPI AG, 2017)
Administered by an oral route, Furosemide (FUR), a diuretic used in several edematous states and hypertension, presents bioavailability problems, reported as a consequence of an erratic gastrointestinal absorption due to various existing polymorphic forms and low and pH-dependent solubility. A mucoadhesive sublingual fast-dissolving FUR based film has been developed and evaluated in order to optimize the bioavailability of FUR by increasing solubility and guaranteeing a good dissolution reproducibility. The Differential Scanning Calorimetry (DSC) analyses confirmed that the film prepared using the solvent casting method entrapped FUR in the amorphous state. As a solid dispersion, FUR increases its solubility up to 28.36 mg/mL. Drug content, thickness, and weight uniformity of film were also evaluated. The measured Young's Modulus, yield strength, and relative elongation of break percentage (EB%) allowed for the classification of the drug-loaded film as an elastomer. Mucoadhesive strength tests showed that the force to detach film from mucosa grew exponentially with increasing contact time up to 7667 N/m2. FUR was quickly discharged from the film following a trend well fitted with the Weibull kinetic model. When applied on sublingual mucosa, the new formulation produced a massive drug flux in the systemic compartment. Overall, the proposed sublingual film enhances drug solubility and absorption, allowing for the prediction of a rapid onset of action and reproducible bioavailability in its clinical application.